A study on the performance of Malaysian Real Estate Investment Trusts from 2005-2010 by using Net Asset Value approach - Ong, Tze San; Teh, Boon Heng; Chong, Mei Pong (2011)
This paper is to understand the definition and the development of REIT in Malaysia and further examine performance of Malaysia REIT based on the Net Asset Value approach (NAV). This study also assesses the noise theory and explains why Malaysia REIT trade at NAV premium and NAV discount. Annual data series for annual closing price of the thirteen listed real estate investment trusts (ARREIT, AXREIT, TWREIT, AMFIRST, BSDREIT, AHP, AHP2, ALAQAR, HEKTAR, UOAREIT, QCAPITAL, ATRIUM and STAREIT) are obtained from the Kuala Lumpur Stock Exchange, also called Bursa Malaysia for the study period from 2005 to 2010. Information about total asset, total liabilities and number of shares outstanding are getting from the 13 MREIT’s respective annual financial report. The result showed that AHP2 has the lowest NAV value among the thirteen listed REIT in Malaysia and traded at NAV discount. This was compatible with the NAV discount in NAV approach. NAV discounts below the current stock prices are reflection of poor current and future prospects for firm earnings, mistakes in financing and operations decision. AXREIT is traded at NAV discount due to the irrational behaviour of investors in noise trader theory and not because it’s poor performance. Investors are overly optimistic about AXREIT according to noise theory. Overall, MREIT are traded at NAV premium. In conclusion, MREIT are generally much better companies in terms of disclosure, transparency, share liquidity, corporate democracy and depth of management.